2023
DOI: 10.1007/s11356-023-30665-8
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-assisted enzyme-induced carbonate precipitation for immobilizing Cu ions in aqueous solution and loess

Yi-Xin Xie,
Wen-Chieh Cheng,
Lin Wang
et al.

Abstract: Wastewater, discharged in copper (Cu) mining and smelting, usually contains a large amount of Cu 2+ .Immobilizing Cu 2+ in aqueous solution and soils is deemed crucial in preventing its migration into surrounding environments. In recent years, the enzyme-induced carbonate precipitation (EICP) has been widely applied to Cu immobilization. However, the effect of Cu 2+ toxicity denatures and even inactivates the urease. In the present work, the biopolymer-assisted EICP technology was proposed. The inherent mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Biopolymer-assisted Enzyme-Induced Carbonate Precipitation (EICP), this technique utilizes enzymes and biopolymers to precipitate carbonates, effectively immobilizing heavy metals and preventing their migration. Xie et al (2023b) highlighted its wide applicability for heavy metal remediation. Electrokinetic technology coupled with a biological permeable reactive barrier, this method uses electrical currents to drive the movement of contaminants towards a reactive barrier composed of biological materials, where heavy metals are removed and immobilized.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymer-assisted Enzyme-Induced Carbonate Precipitation (EICP), this technique utilizes enzymes and biopolymers to precipitate carbonates, effectively immobilizing heavy metals and preventing their migration. Xie et al (2023b) highlighted its wide applicability for heavy metal remediation. Electrokinetic technology coupled with a biological permeable reactive barrier, this method uses electrical currents to drive the movement of contaminants towards a reactive barrier composed of biological materials, where heavy metals are removed and immobilized.…”
Section: Introductionmentioning
confidence: 99%
“…The technology can effectively improve the mechanical and hydraulic properties of porous materials such as sands and soils by using the filling and cementing effects of the mineralization product calcium carbonate (Ivanov and Chu, 2008;Soon et al, 2013;Chen et al, 2023). Numerous studies have demonstrated that MICP technology shows potential for application in several research fields, such as soil reinforcement, fissure repair, and bio-inspired heavy metal immobilization (Wang K. et al, 2023;Xie et al, 2023;Xue et al, 2023). Meanwhile, It has a wide range of applications in the field of geotechnical engineering ( Chu et al, 2012;Choi et al, 2016;Jiang and Soga, 2017;Xiao et al, 2019;Wu et al, 2019;Wang and Nackenhorst, 2020;Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%